Psychosocial problems and needs of patients in palliative care center - Mithrason, Arun T.; Parasuraman, Gomathy; Iyer, Ramesh Harihara; Varadarajan, Suresh (International Journal Of Community Medicine And Public Health, 2018)
Background: Number of cancer cases in India is rising every year and also the sufferings caused by the disease. The patients not only require physical control of disease and symptoms, but, also need help to cope up with other elements caused by the disease. Psychosocial aspect of the patient is usually left unmet. Methods: This study was done in ‘Jeevodaya Hospice Care Centre’, Chennai, India. 60 patients were included in this study. Questionnaire on problems and needs in palliative care was used. The questionnaire consists of eleven elements which deal with psychological issues and fourteen elements which deal with social problems and needs. Results: The five most common psychological problems, perceived by palliative care patients in descending order were; depressed mood (96.7%), fear of metastasis (95%), unpredictability of future (93.3%), not experiencing pleasure (91.5%), and, fear of physical suffering (85%). The five most common social problems perceived by the patients were; loneliness (93.3%), experiencing too little support from others (61.7%), difficulty in talking about the disease for not wanting to bother others (56.7%), finding others not receptive while talking about the disease (53.3%) and difficulty in finding someone confidential to talk to (46.7%). Conclusions: These psychological and social problems along with fear of death causes disruption of the sensitive balance between the body and mind. Proper communication, treatment and counselling helps in a great way to tackle such issues.